Projetos e programas sociais esportivos no Brasil: histórico, estado da arte e contribuições do programa segundo tempo - Kravchychyn, Claudio (2014)
The government priority and the design of educational sports are strong influential factors to the formation of social projects and sports programs in Brazil. The objective of this thesis was to analyze the design of educational sport, its materialization in the projects, sports social programs and contributions to the "Segundo Tempo" Program in this context. Three items make up the thesis. The first, a narrative review, aimed to identify original factors, expansion and consolidation of projects and sports social programs in the Brazilian sports field. Original and outstanding factors are the recognition of the educational potential of sport and the priority of government social policies for children, adolescence and youth. As expansion and consolidation factors, there are the infra-constitutional laws and the creation of the Ministry of Sports. The second, as a systematic review aimed at presenting the state of art projects and Brazilian social sports programs from the scientific production made in the field of physical education. Thirty-eight original articles published between 2004 and 2013 were selected and categorized. It was concluded that the articles have prioritized pedagogical aspects by documenting the contribution of the area of physical education in various national realities. The third article is a descriptive study aimed at analyzing the "Segundo Tempo" Program as a pedagogical model of development of educational sports. Regarding the development of the proposal and partnership with universities, the development and improvement of shares of the theoretical framework and pedagogical actions along with covenants were described and analyzed. It was concluded that the process described is subject to reference public policies of educational sport in Brazil. In general, it is believed that there is a strong link among the projects, sports social programs in Brazil, the principles of sport education, and a lack of educational proposals for the realization of such principles. The contribution to the "Segundo Tempo" Program is through the development of a pedagogical proposal that meets this need.